“To Assess The Knowledge And Practices Regarding Rehabilitation Among Post-Covid Patients Of Selected Areas In Sangli Miraj Kupwad Corporation Area.” (Journal of Pharmaceutical Negative Results, 2022)
“A study to assess the knowledge and practices regarding rehabilitation among post-covid patients of selected areas in Sangli Miraj Kupwad Corporation area.”A quantitative study was carried out with the purpose of finding out the knowledge and practice score.Objectives of the study are:1) To assess the existing knowledge regarding rehabilitation among post-covid patients.2) To assess the existing practices regarding rehabilitation among post-covid patients.3) To find out the association between existing knowledge and practice score with selected demographic variables.A present study was conducted by using quantitative approach with non-experimental descriptive research design. The conceptual framework was based on Nola J Penders health promotion model revised in 1996 with individual characteristics, activities related effect, commitment to plan of action and behavioural outcomes. The reliability was done by split half method ‘r’ was calculated by using formula coefficient corelation ‘r’ of the questionnaire was 0.83and practice checklist was 0.72 which is more then 0.7 hence it was found to be reliable.Validity was done from 20 experts. Proposal with tool presented infront of ethical committee for permission.Total 276 samples were selected by non-probability simple random sampling method.The Chi-square was used to see the association between the demographic variables with the level of Knowledge. The test was conducted at 5% level of significance, assuming the null Hypothesis, that there will be no significant association between level of Knowledge with demographic variables.For the demographic variable education, the p value of the association test with level of Knowledge was less than 0.05. That means, the level of Knowledge of post Covid patients is associated with education. Concludes that, there was significant association of education with the level of Knowledge.For the demographic variables, age, gender, previous knowledge, etc. the p value of the association test with level of Knowledge was more than 0.05. That means, the level of Knowledge of post Covid patients is not associated with these demographic variables. Concludes that, there was no significant association of these demographic variables with the level of Knowledge.The Chi-square was used to see the association between the demographic variables with the level of Practice. The test was conducted at 5% level of significance, assuming the null Hypothesis, that there will be no significant association between level of Practice with demographic variables.For the demographic variables age, gender, education and previous knowledge, the p value of the association test with level of practice was less than 0.05. That means, the level of practice of post Covid patients is associated with these demographic variables. Concludes that, there was significant association of age with the level of practice.For the remaining demographic variables like, are you vaccinated and doses they received, the p value of the association test with level of Practice was more than 0.05. That means, the level of Practice of post Covid patients is not associated with these demographic variables. Concludes that, there was no significant association of these demographic variables with the level of Practice.